Effect Of Tiwul Flour Substitution And Moringa Puree Addition On Soft Cookies Sensory Characteristics - Aurellia fitri Ramadhani (Jurnal Pendidikan Tata Boga dan Teknologi, 2026)
This investigation is intended to ascertain the influence exerted by work motivation and the working milieu on the performance of employees.The participants involved in this inquiry comprise staff members of Bank Kalsel Main Branch Office in Banjarmasin. The sampling procedure employed saturated sampling, whereby the entirety of the population elements was incorporated as the research sample. Data were gathered through the administration of structured questionnaires, while the analytical approach applied was multiple linear regression. The findings of the investigation indicate that work motivation and the work environment, when considered concurrently, demonstrate a statistically significant impact on employee performance. Work motivation exhibits a favorable and direct contribution to employee performance. Likewise, the work environment also reveals a constructive and positive influence on employee performance. Data processing was executed through the utilization of a Two-Way ANOVA procedure, subsequently followed by DMRT at a 95% confidence level. In light of the empirical findings, a statistically meaningful effect was observed in the color attribute (p<0.05), attributable to the substitution of tiwul flour alongside the incorporation of moringa leaf puree, whereas the parameters of aroma, taste, and texture did not exhibit any statistically significant variation (p>0.05). The most favorable formulation was attained with the application of 60% tiwul flour and 30% moringa leaf puree, yielding the highest overall preference score of 3.45 on a 1–4 hedonic scale. In terms of nutritional composition, the product comprises 6.23% protein, 77.06% carbohydrates, 182.45 mg calcium, 91.44 mg magnesium, and 53.60 mg vitamin C. These results suggest that the product demonstrates commendable sensory quality and holds prospective potential for advancement as a functional food derived from indigenous resources